The Treatment Status of Patients in NSCLC With RET Fusion Under the Prelude of Selective RET-TKI Application in China: A Multicenter Retrospective Research - Meng, Yan; Yang, Yilin; Fang, Yujia; Lin, Xinqing; Xie, Xiaohong; Deng, Haiyi; Wu, Jianhui; Zhou, Maolin; Sun, Ni; Xie, Zhanhong; Liu, Ming; Ouyang, Ming; et al. (Frontiers in Oncology, 2022)
Background Rearranged during transfection (RET) fusion is a kind of uncommon mutation (about 1%) in non-small cell lung cancer (NSCLC). Although selective tyrosine kinase inhibitors (TKI) (selpercatinib and pralsetinib) have been available, there are no real-world data about the difference in the efficacy between RET-TKI and other regimens in China. Methods We conducted a multicenter retrospective analysis of 49 patients with RET-fusion-positive NSCLC. The characteristics and the clinical outcomes with RET-TKI, multi-kinase inhibitor (MKI), systematic chemotherapy, and immune-checkpoint inhibitor (ICI)-based regimens were evaluated. Results Of the 92 treatments in patients included, RET-TKI was administered 24 times (26.1%), systematic chemotherapy was 35 times (38.0%), ICI-based regimens was 26 times (28.3%), and MKI was 7 times (7.6%). RET-TKI had a higher objective response rate than the chemotherapy and ICI-based regimens (63.6% vs. 14.3% vs. 21.0%, p < 0.001). The median progress-free survival (mPFS) of RET-TKI, chemotherapy, immunotherapy, and MKI was 16.9 (95% CI: 1.8–32.0) months, 11.9 (95% CI: 7.7–16.1) months, 6.7 (95% CI: 2.9–10.5) months, and 2.8 (95% CI: 1.1–4.4) months, respectively. The mPFS of RET-TKI was longer than MKI and immunotherapy (p < 0.001), while without difference with chemotherapy (p = 0.096). Moreover, chemotherapy had longer mPFS than MKI (p < 0.001). In subgroup analysis, patients with brain metastases in RET-TKI treatment had worse mPFS than the one of patients without brain metastases (6.1 (95% CI: 0.0–13.9) months and 8.5 (95% CI: 6.3–10.6) months, p = 0.012). For patients having chemotherapy with or without angiogenesis inhibitors, the mPFS was 12.0 (95% CI: 11.05–13.02) months and 9.1 (95% CI: 8.31–9.89) months (p = 0.468). In the group of ICI-based regimens, the expression level of PD-L1 did not affect the mPFS of ICI [PD-L1 (+) vs. PD-L1 (–): 4.7 (95% CI: 1.8–9.0) months vs. 7.6 (95% CI: 1.1–14.0) months, p = 0.910]. For overall patients, ECOG PS score, therapy lines, and therapeutic regimens were the independent factors affecting the prognosis. Conclusions In RET-fusion-positive NSCLC, RET-TKI is the best choice for a better response rate and PFS. In addition, chemotherapy which may bring a good PFS, is still a good choice for this group of patients.